Ação da laserterapia no infarto do miocárdio induzido por oclusão da artéria coronária em ratas: análise do perfil de expressão gênica - Feliciano, Regiane dos Santos (2015)
Myocardial infarction (MI) in rats promoted by occlusion of the anterior descending coronary artery is the most widely used experimental model in research that seeks to elucidate the functional, structural and molecular changes associated with ischemic heart disease. Recently, low-level laser therapy (LLLT) has become an alternative therapy to modulate various biological processes and depending on the wavelength, dosage and condition of the irradiated tissue, has anti-inflammatory effect, reduces pain and accelerate cell proliferation. Thus, we evaluated in experimental rats that underwent coronary artery occlusion after irradiation with therapeutic laser myocardial function by echocardiography. Also an analysis was carried out "in-silico", using bioinformatics tools to verify genes involved in metabolic pathways related to MI in rats. After searching the databases, 47 genes of 9 metabolic pathways (Angiogenesis and cell survival, hypertrophy, oxidative stress, apoptosis, extracellular matrix, the Cálcio kinetics, cell metabolism and inflammation) were associated with MI. The changes in gene expression that occur in the myocardium were analyzed by PCR array Real Time. The Group Myocardial Infarction (MI), and the Group Infarction + Laser (MI + Laser) when compared to the control group (Sham), showed 22 (44.60%) and 12 (25.53%) of differentially expressed genes respectively. The results of this study suggest that laser therapy was able to modulate various post-infarction processes, including apoptosis, inflammation, cardiac hypertrophy, cell metabolism and especially the ECM composition in cardiac remodeling. The data obtained here, although complex, indicate genes of interest and certainly allow further analysis of potential key genes in cellular response. Thus, this screening of the initial expression profiles ensures more in-depth studies to confirm and explain the role of each gene or group of genes involved in acute myocardial infarction.